(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of this study is to investigate the antidepressant effects of Mentha pulegium essential oil in BALB/c mice. Six experimental groups (7 mice each) were used. Forced swim test was performed 30 min after essential oil injection. In the groups receiving M. pulegium essential oil (50, 75 and 100 mg/kg), immobility duration significantly decreased compared to the control group. M. pulegium (50 and 75 mg/kg) resulted in significant decrease in nitrate/nitrite content in serum compared to the control group. M. pulegium essential oil antidepressant effect that may be due to the inhibition of oxidative stress. The results showed that decrease in nitrate/nitrite content in serum and high antioxidant effects of M. pulegium essential oil. Video Clip of Methodology: Immobility in Forced Swim Test: 13 sec Click to watch Mobility in Forced Swim Test: 19 sec Click to watch